AN ANALYSIS OF TEACHER’S COMMUNICATION TECHNIQUE IN TEACHING ENGLISH TO YOUNG LEARNERS - Irmayanti Irmayanti; Abdul Halim; Tri Indah Rusli (Metacommunication, 2018)
This study aimed to reveal the teaching techniques that are used by the teacher in teaching English to Young Learners (TEYL) at SDN 3 Baruga Kendari. This study applied descriptive qualitative design. Subject of this study is the teacher of class 4A in SDN 3 Baruga. She was taken through purposive sampling technique. To obtain the data it used observation sheet and interview. The observation was conducted to identify the teaching techniques that were applied by the teacher in teaching EYL. The interview was enabling the writer to recheck the data of the process of classroom by looking at teachers’ point of view. The result of the study indicated that the teacher used seven techniques namely listen and repeat, question and answer, listen and do, draw and color, brainstorming, pair work and group discussion. Those techniques were reliable to be applied in teaching EYL. Among those techniques the teacher mostly applied listen and repeat. This technique helped students to remember what they had learned easily and stimulated students’ sense of listening. Considering the advantages of listen and repeat, it could be teacher’s opinion to make effective the teaching and learning process in order to increase students’ ability.Keywords: Teachers’ Technique, Teaching EYL